Particle identification with the LHCb RICH system - Harnew, N; Collaboration, LRICH (2006)
The LHCb experiment uses a Ring Imaging Cherenkov (RICH) system to provide particle identification over the momentum range 2-10OGeV/c. Two RICH detectors are employed. The upstream detector, RICH 1, utilizes both aerogel and C4F10 gas radiators whilst the downstream RICH 2 uses a CF4 gas radiator. The RICH 2 detector has been fabricated and is installed in the LHCb interaction region; RICH 1 has a programme of phased design and construction. Novel Hybrid Photon Detectors (HPDs) have been developed in collaboration with industry to detect the Cherenkov photons in the wavelength range 200-600 nm. The HPDs are enclosed in iron shielding and Mumetal cylinders to allow operation in magnetic fields up to 50 mT. The performance of pre-series HPDs and the results obtained from a particle test beam using the full LHCb readout chain is presented. The production of a total of 484 HPDs required for the two RICH detectors has recently commenced. The expected performance of the LHCb RICH system, obtained from realistic simulation, is described. (c) 2006 Elsevier B.V. All rights reserved.